Autism and Triadic Play: An Object Lesson in the Mutuality of the Social and Material. Issue 2 (3rd April 2018) - Williams, Emma I.; Costall, Alan; Reddy, Vasu
ABSTRACT: Children's relations to objects are often seen as operating in a physical, asocial realm distinct from the sociocultural realm of other people. The most influential theories of autism exemplify this assumption, emphasizing problems in relating to other people alongside relatively intact dealings with objects. This article challenges the notion of a rigid social-material divide. It examines evidence of widespread disruption in the object use of children with autism, alongside developmental ecological and sociocultural research highlighting the mutuality of our relations to people and things, to argue that difficulties in relating to other people should themselves lead us to expect corresponding problems in object use. In support of this argument findings are presented from an empirical study comparing the triadic (parent-object-infant) play of children with autism (ages 1–6) and their parents to that of developmentally matched typical and Down syndrome dyads. Children's response to parental invitations and the proportion of time each child spent engaged with objects and/or their parents were compared. In contrast to the children in the comparison groups, those with autism were more likely to show no interest in parental invitations to act on an object in a particular way due to being preoccupied with their own use of an object and less likely to comply with such invitations. They also spent less time jointly engaged with their parent and an object and more time unengaged or focused exclusively on their own use of an object. These findings are discussed in the context of Gibson's (1979 ) concept of affordances to further our understanding of the social mediation of object use in children with and without autism and the role unusual child-object relations in autism might play in disrupting ongoing interaction.